Optimization of surface roughness by design of experiment techniques during CNC milling machining. (2022) - Yadav, Deepak Kumar; Dixit, Nitesh Kumar; Agarwal, Deepak; Khare, Sanchit Kumar
Abstract: This paper explores a novel methodology for the improvement of machining boundaries of processing process with different reactions, in light of Taguchi symmetrical exhibit (OA). Trials were directed on titanium combination test examples with uncoated carbide tool. In this research paper, an effort has been made to optimize the cutting parameters in CNC milling operation through various software so that better output response can be obtained. The DOE and the Taguchi method have been used in this experimental work to obtain optimum results for the output responses such as metal removal rate and surface roughness. The analyses were planned and performed utilizing the Taguchi L9 symmetrical exhibit technique. The outcome is examined using analysis of variance (ANOVA). The optimized results are speed = 1200 rpm, feed rate = 7 mm/min, depth of cut = 4 mm and tool diameter = 10 mm produces the optimum value of surface roughness Ra = 0.73 µm. The aftereffects of this review show that the Taguchi strategy can decide the advanced qualities of boundaries in CNC processing.